Pengaruh Pelatihan Tenaga Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Bank Tabungan Negara (Persero), Tbk Cabang Manado - Beby F. A. Purwodono; William A. Areros; Sontje M. Sumayku (Universitas Sam Ratulangi, 2018)
This study aims to determine the influence of labor training on employee productivity and theinfluence of labor training and significant on employee at PT. Bank Tabungan Negara. This must be able to improve the quality of its employee who in their activities provide training and education standards for each employee in improving the quality of the company. This training is carried out for new and old employee also need to learn and be trained with aim of improving unfavorable performance, learning new knowledge and technology and new skills, as well adjusting to the developmentof organizational. Education and training is an important factor in the development of human resources. This research uses quantitative research method with regression analysis approach to know the influence between variables, namely labor training (X) and employee work productivity (Y). This research was conducted directly in the object of research. There are two types of methods used namely observation and questionnaire. With the result of this study indicate that labor training and employee work have a positive and significant influence on employee work and productivity, so significant there is influence of labor training and significant of employee work productivity acceptable and indirectly can provide support for several theories that explain that labor training will affect the increase in employee work productivity.Keywords: Labor training, employee, productivity